2021
DOI: 10.15537/smj.2021.42.9.20210342
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dermatologists’ perception of utilizing teledermatology during COVID-19 pandemic in Saudi Arabia

Abstract: Objectives: To assess teledermatology )TD( perception among dermatologists in the Kingdom of Saudi Arabia during the COVID-19 pandemic and to identify the most common advantages and disadvantages of TD.Methods: We conducted a cross-sectional surveybased study to address Saudi dermatologist perceptions of TD from July 2020 to December 2020, during Covid-19 pandemic.Results: Out of 664 emails sent, 107 complete responses were returned. Approximately 40.2% used TD through Original Article phone calls, followed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…[ 15 ] In another study conducted among dermatologists and dermatological patients, 40.2% of dermatologists used teledermatology, whereas 32.7% utilized a virtual clinic and they concluded that the best benefit of teledermatology was triage of patients before inpatient and outpatient visits, and decrease the risk of infections and almost two-thirds of them (64.5%) will consider using teledermatology in the future. [ 17 ] Abdel Nasser A, et al revealed that approximately half of Saudi patients (52%) were very satisfied with the ease of registration, whereas 43.4% claimed that they had the ability to speak freely over telemedicine. The highest level of satisfaction was observed among almost half of the participants (53.4%) regarding ease registration, 40.1% regarding quality of the visual image, 41.9% regarding the quality of the audio sound, and 44.8% regarding their ability to speak freely over telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 ] In another study conducted among dermatologists and dermatological patients, 40.2% of dermatologists used teledermatology, whereas 32.7% utilized a virtual clinic and they concluded that the best benefit of teledermatology was triage of patients before inpatient and outpatient visits, and decrease the risk of infections and almost two-thirds of them (64.5%) will consider using teledermatology in the future. [ 17 ] Abdel Nasser A, et al revealed that approximately half of Saudi patients (52%) were very satisfied with the ease of registration, whereas 43.4% claimed that they had the ability to speak freely over telemedicine. The highest level of satisfaction was observed among almost half of the participants (53.4%) regarding ease registration, 40.1% regarding quality of the visual image, 41.9% regarding the quality of the audio sound, and 44.8% regarding their ability to speak freely over telemedicine.…”
Section: Discussionmentioning
confidence: 99%
“…While the promise of IPTD has yet to be fully realized, IPTD with SAFT offers a viable means for ameliorating healthcare access inequities [ 19 ••, 21 ]. Concerns about the diminished efficacy of IPTD relative to face-to-face visits for the diagnosis and management of skin disease are largely unfounded, with several survey studies demonstrating consistent patient and provider satisfaction with outpatient and inpatient teledermatology consultation [ 21 , 22 ].…”
Section: Inpatient Teledermatology (Iptd)mentioning
confidence: 99%
“…Many services considered to be non-essential were either discontinued or adapted to a virtual format, and previously underutilized electronic medical record applications for virtual and electronic visits quickly gained traction with providers [ 23 ]. Some hospitals in the USA as well as internationally (e.g., Singapore, Saudi Arabia) transitioned their dermatology visits to virtual encounters through teledermatology platforms [ 16 ••, 22 , 23 , 24 •, 25 , 26 ]. This switch was largely successful, with one study recognizing that the transition helped preserve scarce personal protective equipment (PPE) in the early months of the pandemic and spurred providers to work more efficiently and collaboratively [ 24 •].…”
Section: Inpatient Teledermatology (Iptd)mentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned previously, teledermatology has been used for decades, and studies related to teledermatology have also been conducted. Most of the teledermatology studies address the issue of implementing teledermatology in various countries (Almaziad et al, 2021;Chow et al, 2021;Handa et al, 2021). Other studies discuss the implementation of patient and doctor satisfaction levels in providing services, as well as the level of suitability of services compared to conventional services (Eldaly et al, 2022;Marchell et al, 2017;Santiago & Lu, 2023).…”
Section: Introductionmentioning
confidence: 99%